Applied Computing to Support Industry : Innovation and Technology : First International Conference, ACRIT 2019, Ramadi, Iraq, September 15–16, 2019, Revised Selected Papers /: Innovation and Technology : First International Conference, ACRIT 2019, Ramadi, Iraq, September 15–16, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available